Evaluation of risk management practices in information systems project in the public sector - Badrulhisham Baharuddin,; Maryati Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Risk has been identified as one of the important factors that influences the success of Information Systems projects. Poor risk management could pose a threat to project performance and outcome. Many risk management models and standards have been developed to assist project managers and teams to overcome or minimize the impact of project risk. Despite continuous attention and emphasis on the positive contributions of risk management to a project, risk management practices are relatively lacking and it have not been practiced in its entirety. Hence, this study intended to identify the level of risk management practice and its influencing factors in IS projects. A case study was carried out by adopting the risk management maturity model to evaluate the level of risk management practices in IS projects. Factors that influence risk management practices in IS projects were identified and validated by experts. The findings can be used as a guideline for improving and enhancing implementation of risk management in project development.